Influence of Channel Orientation in Air Coolers on the Efficiency of Heat Removal from Powerful Semiconductor Devices - G. A. Piskun; V. F. Alexeev; A. N. Belikov; D. G. Rybakov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the study of air-cooled coolers with natural and forced heat removal from such powerful semiconductor devices as processors are presented. Experiments were performed in the SOLIDWORKS Flow Simulation software environment to assess the influence of the orientation of the formed thermal channels on the efficiency of heat removal from the surface of a heat-loaded element. Three-dimensional models of tower heatsinks with an installed fan and a supporting structure in the form of heat pipes penetrating fins that form horizontal (model No 1) or vertical (model No 2) air channels have been developed, which made it possible to determine the efficiency of heat removal from the processor during natural and forced convection. The developed model No 1 was rotated by 90°, which may be due to design requirements in the development of technical means. This led to a change in the movement of warm air during natural and forced convection along the vertically directed channels with an analysis of the effectiveness of passive and active cooling. The number of heat pipes has been changed from six to two for previously developed types of radiators (models No 1 and 2), only with active cooling. This made it possible to experimentally establish the influence of design solutions (the number and orientation of heat pipes) in the production of modern air-cooled coolers on the efficiency of heat removal.